7.9k views
2 votes
Find all the zeros of the equation. -x^3-3x^2=6x+4

User Ameya Rote
by
5.3k points

2 Answers

3 votes

Answer:

Explanation:

the answer is A, just took the test

User Kathir
by
5.3k points
2 votes

Answer:

The zeros of given expression
-x^3-3x^2=6x+4 is -1,
-1+i√(3) and
-1-i√(3)

Explanation:

Given expresssion is
-x^3-3x^2=6x+4

To find zeros of given expression we have to equate the expression to zero.

ie.,
-x^3-3^2-6x-4=0


-(x^3+3x^2+6x+4)=0


x^3+3x^2+6x+4=0

By using synthetic division

-1 | 1 3 6 4

| 0 -1 -2 -4

|________________

1 2 4 0

Therefore (x+1) is a zero

Now the quadratic equation is
x^2+2x+4=0

For quadratic equation
ax^2+bx+c=0 we have


x=(-b\pm √(b^2-4ac))/(2a)

Here a=1 ,b=2 and c=4 now substitute the values


x=(-2\pm √(2^2-4(1)(4)))/(2(1))


x=(-2\pm √(4-16))/(2)


x=(-2\pm √(-12))/(2)


x=(-2\pm √(12i^2))/(2) where
i^2=-1


x=(-2\pm i √(4* 3))/(2)


x=(-2\pm i √(4)√(3))/(2)


x=(-2\pm 2i√(3))/(2)


x=2*((-1\pm i√(3)))/(2)


x=-1\pm i√(3)

Therefore
x=-1+i√(3) and
x=-1-i√(3)

Therefore the zeros are -1,
-1+i√(3) and
-1-i√(3)

User Glemiere
by
5.7k points